2018
DOI: 10.1002/celc.201800973
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Flash Fluorination and Radiofluorination

Abstract: A new method for rapid late-stage fluorination using the cation pool technique is presented. Fluorination and no-carrier-added radiofluorination of methyl (phenylthio) acetate, methyl 2-(methylthio) acetate, and methyl 2-(ethylthio) acetate were performed. The carbocations formed through electrochemical oxidation were stabilized by using a divided electrochemical cell and 2,2,2-trifluoroethanol (TFE) as the solvent at −20 °C. At the end of electrolysis, either stable-isotope [19F]fluoride or no-carrier-added r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Indeed, Sadeghi reported in 2017 the electrochemical 18 F-labelling of methyl(phenylthio)acetate under controlled potentiostatic conditions (1.4 V) using [ 18 F]TBAF in the presence of triflic acid; the process afforded methyl 2-[ 18 F]fluoro-2-(phenylthio)acetate in 7% and avoided the use of hydrogen fluoride salts (e.g. Et 3 N•3HF) (Balandeh et al 2018). In 20 18 , this methodology was improved by the use of 2,2,2-trifluoroethanol (TFE) and 2,6-di-tert-butyl-4-methylpyridine, at low temperature (-20 °C) in triflic acid (pH = 3) ( Barata-Vallejo et al 2015).…”
Section: Csp 3 -F Bond Formationmentioning
confidence: 99%
“…Indeed, Sadeghi reported in 2017 the electrochemical 18 F-labelling of methyl(phenylthio)acetate under controlled potentiostatic conditions (1.4 V) using [ 18 F]TBAF in the presence of triflic acid; the process afforded methyl 2-[ 18 F]fluoro-2-(phenylthio)acetate in 7% and avoided the use of hydrogen fluoride salts (e.g. Et 3 N•3HF) (Balandeh et al 2018). In 20 18 , this methodology was improved by the use of 2,2,2-trifluoroethanol (TFE) and 2,6-di-tert-butyl-4-methylpyridine, at low temperature (-20 °C) in triflic acid (pH = 3) ( Barata-Vallejo et al 2015).…”
Section: Csp 3 -F Bond Formationmentioning
confidence: 99%
“…Research on 18 F-labeling by electrosynthesis provides a new direction for investigations into radiofluorination ( Waldmann et al, 2017 ; Hernández-Valdés and Sadeghi, 2021 ). Professor Sadeghi’s group studied the electrochemical fluorination of di- tert -butyl-(4- tert -butyl-1,2-phenylene)-dicarbonate ( He et al, 2015 ) and methyl (phenylthio)acetate ( Balandeh et al, 2017 ; Balandeh et al, 2018 ). These studies led to the invention of an automated apparatus for 18 F-fluorination of organic molecules 16 ( Figure 4 , Reaction 6) by his group ( Waldmann et al, 2017 ), reported to achieve the highest RCY of 17.9%.…”
Section: Transition Metals Catalyzed Radiofluorinationsmentioning
confidence: 99%
“…9 Most electrochemical fluorinations are achieved by an umpolung strategy using oxidation of a target substrate on an anode, followed by the nucleophilic attack of fluoride ions derived from ionic liquid of HF-amine complex 10 or other fluorine sources. 11,12 Electrochemical fluorination is an environmentally friendly and safe method since neither harsh reaction conditions nor equimolar of oxidants are required. However, one inevitable drawback of the electrolysis is the use of a high concentration of supporting electrolytes (> 0.1 M), which results in a large amount of chemical waste as well as the additional steps for purification.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%